Studi Fenomena Multilingual dalam Pembelajaran Bahasa Arab di Brunei Darussalam - Sovinaz; Syamsiyah, Dailatus; Haji Abdul Mutalip, Nur Hidayatul Hamidah binti (Al-Ma‘rifah, 2025)
This study aims to explore the experiences of multilingual students in Brunei Darussalam in learning Arabic, with a focus on the influence of the Melayu Islam Beraja (MIB) culture and identity on the language learning process. Employing a qualitative phenomenological approach, data were collected through observations and interviews. The data analysis followed four stages: data collection, condensation, presentation, and conclusion drawing. The results indicate that the MIB concept plays a significant role in education, with Malay serving as the primary language of instruction and Arabic introduced as part of the Islamic heritage. Students’ experiences suggest that their linguistic backgrounds greatly influence their proficiency and comfort in learning Arabic. Despite the challenges encountered, support from family, lecturers, and close relatives serves as a motivating factor in their efforts to learn and use the Arabic language. These findings underscore the importance of understanding the interplay between multilingualism and culture in the context of language education in Brunei Darussalam, and they highlight the vital role of the MIB philosophy in integrating both Malay and Arabic within the national education system.